PERAN PENGELOLAAN ANGGARAN PEMERINTAH DALAM PEMUDARAN KESENJANGAN PENDIDIKAN DI INDONESIA - Rah Adi Fahmi Ginanjar; Stannia Cahaya Suci; Cep Jandi Anwar; Vadilla Mutia Zahara; Indra Suhendra (Universitas Bina Bangsa, 2021)
This study aims to analyze the convergence process of educational outcomes in Indonesia and determine the role of government budget allocation in accelerating convergence by observing all regions from 2010-2019. According to the results of the σ-convergence analysis, it is found that the dispersion explains the convergence process of the educational index gap. Then confirmed by the results of conditional β-convergence analysis by the System-GMM model, it was found that the convergence speed was relatively slow. This is a consequence of the role of government budget management which has not been optimal. In terms of regional revenues, it is found that the specific purpose transfer and the general purpose transfer have a significant negative effect on the convergence of the education index. Then from the expenditure side, it is known that direct expenditure has a significant positive effect on convergence, while indirect expenditure is not significant. Thus, this evidence opens up opportunities for the educational index to become a separate dimension in determining purpose transfer to the regions to accelerate the convergence of educational outcomes.